Niklas Luhmann : education as a social system - Baraldi, Claudio; Corsi, Giancarlo; Ohio Library and Information Network (Cham, Switzerland : Springer, 2017)
This book provides an insight into the ideas of one of the world's greatest sociologists: Niklas Luhmann. It explains, in clear and concise language, the basic concepts of Social Systems Theory and their application to the specific case of the Education System, which was considered by Luhmann as a primary subsystem of modern society. It illustrates the complex and sophisticated thinking that characterises Luhmann's work and explains that Luhmann's theory has given an important and original contribution to the study of education from a sociological point of view. His contribution has some resonance in recent social constructionist and relational approaches to education, as well as in studies of educational interaction. In addition, research methodologies, in particular mixed methods strategies, draw heavily on epistemological issues. The book finally argues that educationists can appreciate the extent of Luhmann's contribution to the field of education, although their perspective cannot be fully harmonised with, nor reduced to, the sociological one. This divergence of perspectives can stimulate pedagogy to call into question its conceptual framework as well its approach to social situations in the classroom.
Keywords: Luhmann, Niklas, -- 1927-1998.; Education -- Sociological aspects; Social systems; Electronic books